Kinetic Storytelling as a Basis for Designing a Proposed Program and Its Impact on the Development of Some Language Skills in Kindergarten Children - karoum, bachir; benhaffaf, yahia; benkouider, ahmed (El Omda in Linguistics and Discourse Analysis, 2023)
Abstract : Kindergarten is an important and distinct educational stage with its own educational goals and philosophy. Psychologists and educators attach special importance to the childhood stage because it is an important stage in which the social personality of the child or learner is completed and the characteristics of this personality are determined. On this basis, educators must use different teaching methods to care for the child and create the appropriate climate for his growth, and one of these methods is the kinetic story method. We can feel the tendency of the child or the learner to stories, so we tell him stories that include different types of movements that include all parts of the body (moving and static) and ask him to integrate into and represent the atmosphere of the story.